Avaliação do papel do receptor para tromboxanos (TP) durante a epileptogênese - Mello, Fernanda Kulinski (2020)
Convulsive status epilepticus (SE) is a medical emergency that can lead to epilepsy, long lasting brain damage and death. It is known that there is a strong link between epilepsy and inflammation. For instance, it has been shown that epileptic patients have a higher cerebral levels of thromboxane A2 (TXA2) when compared to healthy individuals. The present study aimed to evaluate the role of the thromboxane (TP) receptor after SE, using the TP receptor antagonist SQ 29.548, through behavioral, histological and biochemical assays. C57BL/6 male mice were submitted to the SE induction protocol by the pilocarpine method. After 90 min and 24h from the end of the SE the animals received two doses of the antagonist SQ 29.548 or vehicle via intracerebroventricular (2 μL or 26 nmol / dose) and were evaluated for neuromotor function through the neuroscore test. Astrocytosis and neuronal death were assessed by immunohistochemical staining of GFAP and Fluoro Jade C, respectively. The statistical analysis showed the presence of two distinct groups, responsive and unresponsive to the TP antagonist. Responsive animals performed better in the neuroscore test, had less positive cells for Fluoro-Jade or GFAP in the hippocampus, when compared to animals submitted to SE and treated with vehicle. The results showed that treatment with SQ 29,548 improves neuromotor damage, neuronal death and astrocytosis caused by SE. These neuroprotective effects suggest that the TP receptor may be a possible new target for the treatment of SE and prevention of its consequences.